Development of TPU international cooperation through the formation of international scientific and educational laboratories; Global Engineering Education and Research (GEER), devoyed to the 110th Anniversary of the Foundation of Tomsk Polytechnic University and Cantenary of the First Graduation of Siberian Engineers - Vlasov V. A. Viktor Alekseevich (2006, 2006)
В фонде НТБ ТПУ отсутствует